Systematic risk factors and stock return volatility - Haider, Syed Kamran Ali; Hashmi, Shujahat Haider; Ahmed, Ishtiaq (Applied Studies in Agribusiness and Commerce, 2017)
This study analyzes the transmission of systematic risk exhaling from macroeconomic fundamentals to volatility of stock market by using auto regressive generalized auto regressive conditional heteroskedastic (AR-GARCH) and vector auto regressive (VAR) models. Systematic risk factors used in this study are industrial production, real interest rate, inflation, money supply and exchange rate from 2000-2014. Results indicate that there exists relationship among the volatility of macroeconomic factors and that of stock returns in Pakistan. The relationship among the volatility of macroeconomic variables and that of stock returns is bidirectional; both affect each other in different dynamics. JEL code: C32, C58, G11, G12